Identification of Magma Intrusion Distribution in the Sekincau Mountain Area Based on the Euler Deconvolution Method of Gravity Data: Application of Gravity-Based Euler Deconvolution for Intrusive Mapping - Amanda, Anisa; Agustian, Rizki Buana; Fista, Aksela Dian; Dani, Ilham (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2026)
Mount Sekincau, West Lampung, is located within the active Bukit Barisan tectonic zone and exhibits geothermal potential controlled by magmatic activity and geological structures. This study aims to identify the distribution and depth of magmatic intrusions using gravity data analysis and Euler deconvolution. GGMPlus satellite gravity data were processed to generate Complete Bouguer Anomaly, regional and residual anomalies, analytical signal, Euler solutions, and three-dimensional models. The Complete Bouguer Anomaly values range from 38.05 to 58.32 mGal, with high anomalies concentrated in the central part of the study area. Positive residual anomalies ranging from 0.88 to 2.78 mGal indicate the presence of shallow high-density bodies interpreted as magmatic intrusions. Analytical signal and Euler deconvolution results with a structural index of 0 reveal clusters of shallow sources associated with fault zones. Three-dimensional modeling confirms a southeastward-oriented intrusive body. These results indicate that shallow magmatic intrusions act as the primary heat source of the Sekincau geothermal system.